1998
DOI: 10.1056/nejm199811263392204
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Repeated High Doses and Repeated Standard Doses of Epinephrine for Cardiac Arrest Outside the Hospital

Abstract: In our study, long-term survival after cardiac arrest outside the hospital was no better with repeated high doses of epinephrine than with repeated standard doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(64 citation statements)
references
References 31 publications
4
57
0
3
Order By: Relevance
“…These trials did not demonstrate any benefit for high-dose epinephrine over standard-dose epinephrine for survival to discharge with a good neurologic recovery (ie, Cerebral Performance Category score), 116,117 survival to discharge, [116][117][118][119][120] or survival to hospital admission. [116][117][118]121 There was, however, a demonstrated ROSC advantage with highdose epinephrine.…”
Section: Evidence Summarymentioning
confidence: 92%
“…These trials did not demonstrate any benefit for high-dose epinephrine over standard-dose epinephrine for survival to discharge with a good neurologic recovery (ie, Cerebral Performance Category score), 116,117 survival to discharge, [116][117][118][119][120] or survival to hospital admission. [116][117][118]121 There was, however, a demonstrated ROSC advantage with highdose epinephrine.…”
Section: Evidence Summarymentioning
confidence: 92%
“…To our knowledge, this is the first study depicting such a linear relationship between the dose and outcome, which is consistent with an increasing effect of the ascendant dose of the drug. Some studies have previously shown that repeated and increased doses of epinephrine could worsen the chances of survival(28,29).Before incriminating the drug itself, our findings probably should provoke further discussion on the most appropriate scheme of treatment and its interaction regarding the resuscitation phases. Our sensitivity analyses showed that the role of epinephrine did not change according to ACLS delay or length of resuscitation but was clearly dependent on the timing of first administration.…”
mentioning
confidence: 72%
“…Poor outcomes after cardiac arrest have raised the question of the optimal pharmacological approach to augment circulation during CPR. High-dose epinephrine improves return of spontaneous circulation (ROSC) and hospital admission but there is no difference in long-term survival or neurologic outcome at hospital discharge compared to low-dose epinephrine (3). The use of natural or synthesized vasopressors other than epinephrine has been the subject of many investigations.…”
Section: Introductionmentioning
confidence: 99%